Contemporary analysis of pelvic and para‐aortic metastasis in endometrial cancer using the SEER registry1. Issue 3 (13th August 2014) - Katsoulakis, Evangelia; Mattes, Malcolm D.; Rineer, Justin M.; Nabhani, Thomas; Mourad, Waleed F.; Choi, Kwang; Schreiber, David
Abstract: Objective: To determine the incidence of regional lymph node involvement for early‐stage endometrial cancer by using the Surveillance, Epidemiology, and End Results (SEER) registry. Methods: In a retrospective study, data were analyzed from patients who were diagnosed with stage IA–IIB endometrioid adenocarcinoma and were treated between 1998 and 2003. The incidence of pelvic and para‐aortic lymph node involvement was determined. Results: Data were analyzed from 4052 patients. Incidences of pelvic and para‐aortic lymph node metastases were: 1% and 0% in stage IA, grade 1 disease; 2% and 0% in IA, grade 2; 2% and 1% in IA, grade 3; 2% and 0% in IB, grade 1; 3% and 1% in IB, grade 2; 3% and 2% in IB, grade 3; 7% and 3% in IC, grade 1; 8% and 5% in IC, grade 2; 12% and 8% in IC, grade 3; 7% and 3% in IIA, grade 1; 10% and 4% in IIA, grade 2; 10% and 5% in IIA, grade 3; 8% and 4% in IIB, grade 1; 13% and 8% in IIB, grade 2; and 19% and 12% in IIB, grade 3. Conclusion: Incidences of pelvic and para‐aortic metastases were lower than previously reported. Patients at higher stages and grades had a 10% or higher risk of lymph node involvement and might benefit from aggressive therapy.